MANAGEMENT OF THE BOARDING SCHOOL LEADER IN IMPROVING THE MORALS OF STUDENTS AT SABILIL RASYAD BOARDING SCHOOL - Jayanti, Ani (Conciencia, 2023)
The purpose of this study was to analyse the implementation of boarding school leaders' management in improving the morals of students along with internal and external factors at Sabilil Rasyad Islamic Boarding School. This research method uses a qualitative method. The results of this study found that the implementation of the management of Sabilil Rasyad Islamic Boarding School in Kedurang in the study year included: Management in the aspect of student affairs, namely the admission of new students, intracurricular and extracurricular activities and the release of students who have completed the education level, Management in the aspect of the environment Management in this aspect of the environment is related to the parents of students and community members, Management in the aspect of moral development is carried out by means of; Giving advice, such as reprimanding when doing land, Inviting always to attend majlis ta'lim and telling children to pray diligently.